The Driving Forces Underlying Spatiotemporal Lake Extent Changes in the Inner Tibetan Plateau During the Holocene - Liu, Xiangjun; Madsen, David; Zhang, Xiaojian (Frontiers in Earth Science, 2021)
The Inner Tibetan Plateau (ITP), the central and western part of the Tibetan Plateau (TP), covers about one-fourth of the entire TP and contains more than 800 endorheic lakes larger than 1 km2. These lakes are important water reservoirs and sensitive to TP climate changes. They regulate regional water circulations, and further influence local ecosystems. Many lakes in ITP are surrounded by conspicuous paleoshorelines indicating much higher past lake levels. Previous studies found that lakes in the western ITP (west of ∼86°E) apparently expanded to higher levels than those to the east during the Holocene high lake level stage, however, there is no in-depth study on the reasons for the spatial differences of high lake levels within the ITP. In this study, we first identify Holocene lake level (or lake extent) changes over the ITP by combining published lake level variation data with our reconstruction of Dagze Co lake level variations. We then investigate spatial differences in the magnitude of lake expansions and explore the underlying forces driving these differences using the transient climate evolution of the last 21 ka (TraCE-21ka) and Kiel Climate Model (KCM) simulation results. We find that lakes in the ITP expanded to their highest levels during the early Holocene when the Indian summer monsoon (ISM) greatly intensified. After the mid-Holocene, lake levels fell as a result of the weakening of the ISM. The early Holocene northward shift of the westerly jet and a positive phase of the Atlantic multidecadal oscillation (AMO) resulted in the intensification of southwesterly winds on the southwest TP flank. Concurrently, westerly winds over the TP weakened, causing a differential increase in water vapor transport to the ITP with higher precipitation levels in the southwestern ITP and lower levels to the northeast. These wind-driven differential precipitation levels caused lakes in the southwestern ITP to expand to higher levels than those in the central, northern and northeastern ITP. During the early Holocene, expansion of lakes in the northwestern ITP was enhanced by an increase in glacier melt water besides the increased summer rainfall associated with the intensified ISM.